Will for the formation of students' character in the darmarihistyle of Karya Paku Alam III - Asmuni, Asmuni (Educenter : Jurnal Ilmiah Pendidikan, 2023)
This research explores the will for student character building in "Serat Darmariwayat" by Paku Alam III, a historical figure in Indonesia. In this study, Serat Darmariwayat is designated as the main source to understand the values and teachings left by Paku Alam III regarding character building. It highlights the importance of literature, goodwill, education, self-control, and ethics in shaping a person rooted in local wisdom values. This research presents an in-depth look at how traditional values and literature become the foundation of student character building. This research is library research which specifically focuses on Serat Darmariwayat, a literary work produced by Paku Alam III. it can be assumed that the approach adopted is comprehensive, centered on individual development rooted in cultural, moral and intellectual values. The implications of this will for modern education are significant. The importance of literary appreciation, educational awareness, self-control, and cultural understanding can be applied in today's educational curricula and practices. Although integration challenges may arise, collaborative efforts between educational institutions, local communities and parents can overcome these barriers. This research provides a solid foundation for understanding how traditional values can be a valuable guide in shaping student character in the modern era.